Financial Burden of Health Care Expenditures: Turkey - D Minbay Bernard; S Nur Sulku (Tehran University of Medical Sciences, 2012)
In this study, we examine whether and to what extent the health insurance system in Turkey provided adequate protection against high out of pocket expenditures in the period prior to "The Health Transformation Programme". Furthermore, we examine the distribution of out of pocket expenditures by demographic characteristics, poverty status, health service type, access to health care and self-reported health status. We employ the 2002/03 National Household Health Expenditure Survey data to analyze financial burden of health care expenditure. Following the literature, we define high burdens as expenses above 10 and 20% of income. We find that 19%  of the nonelderly population were living in families spending more than 10% of family income and that 14% of the nonelderly population were living in families spending more than 20% of family income on health care. Furthermore, the poor and those living in economically less developed regions had the greatest risk of high out of pocket burdens. The risk of high financial burdens varied by the type of insurance among the insured due to differences in benefits among the five separate public schemes that provided health insurance in the pre-reform period. Our results are robust to three alternative specifications of the burden measure and including elderly adults in the sample population. We see that prior to the reforms there were not adequate protection against high health expenditures. Our study provides a baseline against which policymakers can measure the success of the health care reform in terms of providing financial protection.